In situ synthesis and surface functionalization of gold nanoparticles with curcumin and their antioxidant properties: an experimental and density functional theory investigation - Singh, Dheeraj K.; Jagannathan, Ramya; Khandelwal, Puneet; Abraham, Priya Mary; Poddar, Pankaj (Nanoscale, 2013)
Curcumin ((1E,6E)-1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione) is an active component of turmeric; it is responsible for its characteristic yellow color and therapeutic potential, but its poor bioavailability remains a major challenge. In order to improve the bioavailability of curcumin, various approaches have been used. One of the possible approaches to increase the bioavailability of curcumin is its conjugation on the surface of metal nanoparticles. Therefore, in the present study, we report the binding of curcumin on the surface of gold nanoparticles (AuNPs). The AuNPs were synthesized by the direct reduction of HAuCl4 using curcumin in the aqueous phase, without the use of any other reducing agents. We found that curcumin acts both as a reducing and capping agent, stabilizing the gold sol for many months. Moreover, these curcumin-capped AuNPs also show good antioxidant activity which was confirmed by the DPPH (2,2-diphenyl-l-picrylhydrazyl) radical test. Thus, the surface functionalization of AuNPs with curcumin may pave a new way of using the curcuminoids towards possible drug delivery and therapeutics. Apart from the experimental study, a detailed quantum chemical calculation using density functional theory (DFT) has been performed, in order to investigate the formation of a complex of curcumin with Au3+ ions in different possible conformational isomeric forms. Our theoretical calculations indicate the evidence of electron transfer from curcumin into the Au center and essentially indicate that as a consequence of complexation, Au3+ ions are reduced to Au-0. Our theoretical results also propose that it is the breakage of intramolecular H-bonding that probably leads to the increased availability of curcumin in the presence of gold ions and water molecules.

Modulation of reaction kinetics for the tuneable synthesis of gold nanoparticles and quantum clusters: application of gold quantum clusters as ``turn-off'' sensing probe for Sn4+ ions - Khandelwal, Puneet; Singh, Dheeraj K.; Sadhu, Subha; Poddar, Pankaj (ChemPlusChem, 2014)
The syntheses of gold nanoparticles (Au NPs) and gold quantum clusters (Au QCs) that employ cefadroxil (CFX; an antibiotic) as both reducing and capping agents are reported. The HAuCl4/CFX concentration, temperature, and pH are crucial factors in the modulation of the nucleation and growth kinetics of the reaction, and consequently, in guiding the size and morphology of as-synthesized Au NPs. Interesting results are observed if the reaction is performed under different pH conditions. TEM analysis of the Au NPs synthesized at pH 6 shows an average particle size of approximately 2 nm along with a relatively smaller population of bigger NPs (up to 6 nm). The Au QCs were isolated by high-speed centrifugation and showed fluorescence at lambda approximate to 460 nm. Furthermore, the as-synthesized Au QCs were applied as sensor for Sn4+ ions on the basis of an aggregation-induced fluorescence quenching mechanism. These Au QCs offer acceptable sensitivity, high selectivity, and a limit of detection of approximately 10 mm for the determination of Sn4+ ions.

Biomilling of rod-shaped ZnO nanoparticles: a potential role of saccharomyces cerevisiae extracellular proteins - Sharan, Chandrashekhar; Khandelwal, Puneet; Poddar, Pankaj (RSC Advances, 2015)
There is a tremendous interest in newly-discovered, green, room-temperature, biological routes for the fabrication of biologically-benign functional nanostructures. The bottom-up biogenic synthesis, where the precursor molecules form crystalline solids at the nanoscale by a redox process, has been validated over the years and gained its popularity. However, a new top-down technique has recently been developed by our group, in which small isotropic nanoparticles (NPs) are formed by the break-down of chemically-synthesized anisotropic rod or plate-shaped NPs using microbes (termed as biomilling). This technique, which holds great promise, is still in its infancy. Here, an improved process with an easy isolation of NPs from the biomass and better control of the technique is reported. This novel technique is demonstrated to break-down the chemically synthesized ZnO nanorods (NRs), similar to 250 nm in length, to small quasi-spherical ZnO NPs (similar to 10 nm in diameter) possibly due to the proteins secreted by the yeast (Saccharomyces cerevisiae), which also led to the formation of `` corona'' around the NPs. The UV-vis, PL and FTIR results show the dynamic nature of the protein corona, which is further supported by the SDS-PAGE study of the extracellular proteins. The SDS-PAGE study of the intracellular proteins shows the over-expression of a single protein which is supposed to have a role in zinc transport in the cells. The ICP-OES results show the accumulation of a higher amount of zinc in the yeast cells as biomilling progresses, while the extracellular zinc contents were almost same. Therefore, we believe that the yeast cells play an important role in the biomilling process by secreting the proteins and maintaining the zinc content in the extracellular fluid. The biomilled NPs exhibit a uniform dispersity and better aqueous stability than chemically synthesized ZnO NRs.

Mechanistic insight into the biomilling of goethite (alpha-FeO(OH)) nanorods using the yeast Saccharomyces cerevisiae - Sharan, Chandrashekhar; Khandelwal, Puneet; Poddar, Pankaj (RSC Advances, 2015)
Since the last decade, eco-friendly routes for the synthesis of nanostructured materials of various types and functionalities have been a topic of enormous interest in the field of nanotechnology. The primary work in this field started with the `bottom-up' microbial synthesis of nanoparticles, however, the bioleaching potential of microbes was initially overlooked in this research. The bioleaching process is useful especially where the synthesis of particles with size < 10 nm is challenging. In the present work, the mechanistic insight of biomilling for a gradual transformation of anisotropic alpha-FeO(OH) rod-shaped particles into isotropic nanoparticles below 10 nm size has been explored using detailed UV-vis spectroscopy, transmission electron microscopy, atomic force microscopy, X-ray diffraction, and X-ray photoelectron spectroscopic studies which suggest that the aquo group present at the alpha-FeO(OH) surface may provide the site for interaction with carboxyl ions of protein molecules which results in the formation of a stable coordination compound with Fe3+ ions. This will create a new Fe3+ ion on the surface of the lattice which leads to the repetition of the process of protein complexation with Fe3+ ions and dissociation of the complex from the lattice that causes the fragmentation of bigger nanoparticles into protein functionalized smaller nanoparticles.

New insights into in vitro amyloidogenic properties of human serum albumin suggest considerations for therapeutic precautions - Sharma, Neetu; Sivalingam, Vishwanath; Maurya, Sonalika; Prasad, Archana; Khandelwal, Puneet; Yadav, Subhash Chandra; Patel, Basant K. (Febs Letters, 2015)
Amyloid aggregates display striking features of detergent stability and self-seeding. Human serum albumin (HSA), a preferred drug-carrier molecule, can also aggregate in vitro. So far, key amyloid properties of stability against ionic detergents and self-seeding, are unclear for HSA aggregates. Precautions against amyloid contamination would be required if HSA aggregates were self-seeding. Here, we show that HSA aggregates display detergent sarkosyl stability and have self-seeding potential. HSA dimer is preferable for clinical applications due to its longer retention in circulation and lesser oedema owing to its larger molecular size. Here, HSA was homodimerized via free cysteine-34, without any potentially immunogenic cross-linkers that are usually pre-requisite for homodimerization. Alike the monomer, HSA dimers also aggregated as amyloid, necessitating precautions while using for therapeutics. (C) 2015 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
Keywords: Drug carrier; HSA amyloid; Plasma expander; Sarkosyl; Self-seeding

Study of the nucleation and growth of antibiotic labeled Au NPs and blue luminescent Au-8 quantum clusters for Hg2+ ion sensing, cellular imaging and antibacterial applications - Khandelwal, Puneet; Singh, Dheeraj K.; Sadhu, Subha; Poddar, Pankaj (Nanoscale, 2015)
Herein, we report a detailed experimental study supported by DFT calculations to understand the mechanism behind the synthesis of cefradine (CFD - an antibiotic) labeled gold nanoparticles (Au NPs) by employing CFD as both a mild reducing and capping agent. The analysis of the effect of growth conditions reveals that a higher concentration of HAuCl4 results in the formation of an increasing fraction of anisotropic structures, higher temperature leads to the formation of quasi-spherical particles instead of anisotropic ones, and larger pH leads to the formation of much smaller particles. The cyclic voltammetry (CV) results show that when the pH of the reaction medium increases from 4 to 6, the reduction potential of CFD increases which leads to the synthesis of nanoparticles (in a pH 4 reaction) to quantum clusters (in a pH 6 reaction). The MALDI-TOF mass spectrometry results of supernatant of the pH 6 reaction indicate the formation of [Au-8(CFD)(2)S-6] QCs which show fluorescence at ca. 432 nm with a Stokes shift of ca. 95 nm. The blue luminescence from Au-8 QCs was applied for sensing of Hg2+ ions on the basis of an aggregation-induced fluorescence quenching mechanism and offers good selectivity and a high sensitivity with a limit of detection ca. 2 nM which is lower than the detection requirement of 10 nM by the U.S. EPA and 30 nM by WHO for drinking water. We have also applied the sensing probe to detect Hg2+ ions in bacterial samples. Further, we have investigated the antibacterial property of as-synthesized Au NPs using MIC, growth curve and cell survival assay. The results show that Au NPs could reduce the cell survival very efficiently rather than the cell growth in comparison to the antibiotic itself. The scanning electron microscopy study shows the degradation and blebbing of the bacterial cell wall upon exposure with Au NPs which was further supported by fluorescence microscopy results. These Au NPs did not show reactive oxygen species generation. We believe that the bacterial cytotoxicity is due to the direct contact of the Au NPs with bacterial cells.

Hydralazine inhibits amyloid beta (Aβ) aggregation and glycation and ameliorates Aβ1–42 induced neurotoxicity - Batkulwar, Kedar B.; Jana, Asis K.; Godbole, Rashmi K.; Khandelwal, Puneet; Sengupta, Neelanjana; Kulkarni, Mahesh J. (RSC Advances, 2016)

Immobilization of multivalent glycoprobes on gold surfaces for sensing proteins and macrophages - Gade, Madhuri; Khandelwal, Puneet; Sangabathuni, Sivakoti; Bavireddi, Harikrishna; Murthy, Raghavendra Vasudeva; Poddar, Pankaj; Kikkeri, Raghavendra (Analyst, 2016)
The multivalent display of carbohydrates on the cell surface provides cooperative binding to improve the specific biological events. In addition to multivalency, the spatial arrangement and orientation of sugars with respect to external stimuli also trigger carbohydrate-protein interactions. Herein, we report a non-covalent host-guest strategy to immobilize heptavalent glyco-beta-cyclodextrin on gold-coated glass slides to study multivalent carbohydrate-protein interactions. We have found that the localization of sugar entities on surfaces using beta-cyclodextrin (beta-CD) chemistry increased the avidity of carbohydrate-protein and carbohydrate-macrophage interactions compared to monovalent-beta-CD sugar coated surfaces. This platform is expected to be a promising tool to amplify the avidity of sugar-mediated interactions on surfaces and contribute to the development of next generation bio-medical products.

Fluorescent metal quantum clusters: an updated overview of the synthesis, properties, and biological applications - Khandelwal, Puneet; Poddar, Pankaj (Journal of Materials Chemistry B, 2017)
Metal quantum clusters are evolving as excellent systems for a wide range of biological applications due to their small size (similar to 2 nm), tunable optical properties, including optical absorption, photoluminescence (UV to NIR), nonlinear optical properties (two-photon absorption, two-photon fluorescence, and second/third harmonic generation), ultrafast dynamics (relaxation kinetics, electron-phonon coupling, and radiative emission), and magnetism. These excellent properties have resulted in their use in a broad range of applications, including the sensing of ions (heavy metal ions, anions), biomolecules (proteins, DNA, miRNA, and enzymes), biological cells, diagnosis, and therapy. This article presents an introduction to metal quantum clusters, including a brief history of research in this system and an overview of the existing theories to understand their properties. We also discuss the synthesis methods, the various properties of quantum clusters and present a broad and updated overview of the applications of metal quantum clusters in biology.

Oxidant mediated one-step complete conversion of multi-walled carbon nanotubes to graphene quantum dots and their bioactivity against mammalian and bacterial cells - Biswas, Anupam; Khandelwal, Puneet; Das, Raja; Salunke, Gayatri; Alam, Aftab; Ghorai, Suvankar; Chattopadhyay, Samit; Poddar, Pankaj (Journal of Materials Chemistry B, 2017)
It is essential for any antibacterial agent (for clinical applications) that it should have high and selective toxicity towards bacterial cells only, and should not affect the human cells at the concentration used. Graphene quantum dots (GQDs) have emerged as a potential candidate for biomedical applications. However, a simple, low cost, safe, easy to execute, one-step synthesis of uniform and monodispersed GQDs with selective toxicity towards bacterial cells rather than mammalian cells is difficult to achieve. Herein, we have reported a one-step, low-cost, aqueous-phase, simple approach for the complete conversion of multi-walled carbon nanotubes into water-dispersible GQDs with an average size of similar to 3 nm using sodium bismuthate (NaBiO3) as a strong oxidant. The cyclic voltammetry and X-ray photoelectron spectroscopy results indicated that the as-synthesized GQDs suspension possess almost negligible amounts of metallic impurities. The cytotoxicity studies of GQDs against mammalian NIH 3T3 (mouse embryo fibroblast cells) and HEK 293T (human embryonic kidney cells) cells showed that the as-synthesized GQDs were non-cytotoxic up to the concentration of similar to 200 mu g mL(-1). The antimicrobial study shows that the synthesized GQDs have high and selective toxicity towards bacterial cells with a minimum inhibitory concentration of similar to 256 mu g mL(-1) for E. coli and B. subtilis and similar to 512 mu g mL(-1) for P. aeruginosa and S. aureus. The scanning electron microscopy and atomic force microscopy images show extensive cell damage via the perturbation of bacterial cell walls, which was consistent with the enhancement of reactive oxygen species production by almost two times in the bacterial cells upon incubation with similar to 256 mu g mL(-1) GQDs. Our study suggested that the as-synthesized GQDs can be used as a potential candidate for clinical applications as they possess high toxicity to bacterial cells and low toxicity to mammalian cells.

Retention of anticancer activity of curcumin after conjugation with fluorescent gold quantum clusters: an in vitro and in vivo xenograft study - Khandelwal, Puneet; Alam, Aftab; Choksi, Arpankumar; Chattopadhyay, Samit; Poddar, Pankaj (ACS Omega, 2018)
Gold nanoparticles (Au NPs) have been thoroughly investigated for anti-cancer therapy. However, their undesired high gold content remains a problem when injected into the body for drug delivery applications. In this report, we made an effort to conjugate the curcumin molecules on the surface of gold quantum clusters (Au QCs) by a novel in situ synthesis method which provides an alternative route to not only reduce the metallic content but also increase the water solubility of curcumin and the loading efficiency. Here, curcumin itself acts as a reducing and capping agent for the synthesis of Au QCs. The UV−vis absorption, fluorescence, transmission electron microscopy, and electrospray ionization mass spectrometry results confirmed the synthesis of fluorescent Au QCs. Curcumin-conjugated Au NPs (C-Au NPs) and glutathione (GSH)-conjugated Au QCs (GSH-Au QCs) were also synthesized to visualize the effect of particle size and the capping agent, respectively, on the cytotoxicity to normal and cancer cells. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay showed that the curcumin-conjugated Au QCs (C-Au QCs) were less cytotoxic to normal cells while almost the same cytotoxic to cancer cells in comparison to curcumin itself, which indicates that curcumin preserves its anticancer property even after binding to the Au QCs. However, C-Au NPs and GSH-Au QCs did not show any cytotoxicity against the normal and cancer cells at the concentration used. The western blot assay indicated that C-Au QCs promote apoptosis in cancer cells. Further, the in vivo study on severe combined immunodeficiency mice showed that C-Au QCs also inhibited the tumor growth efficiently without showing significant toxicity to internal organs.

Advances in the experimental and theoretical understandings of antibiotic conjugated gold nanoparticles for antibacterial applications - Khandelwal, Puneet; Singh, Dheeraj K.; Poddar, Pankaj (ChemistrySelect, 2019)
The worldwide bacterial resistance to a wide range of antibiotics originates a global health concern and calls for the development of new antibacterial agents. Over the recent years, nanomaterials-based agents have been proven to be useful for the effective antibacterial applications. Notably, the gold nanoparticles (AuNPs) draw particular attention due to their biological inertness and easy surface functionalization. It is now established that the antibiotic functionalization on the AuNPs surfaces increases the antibacterial efficacy even towards the antibiotic-resistant bacterial cells. Moreover, the antibacterial efficacy can be further enhanced by photothermal therapy using antibiotic conjugated AuNPs. In this review article, we have reviewed the advances in the development of the synthesis methods of antibiotic conjugated AuNPs and gold nanoclusters, and their antibacterial efficacy. We have also discussed the developments in the theoretical understandings behind the interaction of antibiotic molecules with gold surface and its relation to the antibacterial activity. We believe that few parameters including the selection of antibiotic molecules, the method of its attachment to AuNPs, the purification of antibiotic conjugated AuNPs, and the quantification of conjugated antibiotic are crucial and needs to be properly addressed. Moreover, there are many other future directions discussed, for using antibiotic conjugated AuNPs more effectively for antibacterial therapy.
Keywords: Antibacterial; antibiotic; DFT calculations; gold nanocluster; Gold nanoparticle; multi-drug resistance; photo-thermal therapy